Pengembangan Sistem Manajemen Layanan Pernikahan Berbasis Web (Studi Kasus: KUA Dawarblandong - Mojokerto) - Nadya Dwi Sukmawati; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Office of Religious Affairs has a role in religious matters, especially marriage. In improving the function, KUA Dawarblandong use the "SIMKAH" website for marriage registration, but candidates must also come to KUA to register and complete the offline registration process to KUA. However, it can interfere with other KUA services such as referral and isbat registration which is still done with offline, because because of the large queue at the time of the wedding season comes and also the processing of schedules for the trial is irregular. From this problem, encourage researchers to develop a web-based marriage service management system with the PHP programming language and Codeigniter framework using the waterfall method and use the Whatsapp Gateway API to receive information. This method begins with requirements engineering, design, implementation, testing and maintenance. This research can produce in 44 functional requirements, 1 non-functional requirement, unit testing, integration and validation to get 100% valid test cases, and this system can be accessed in different web browsers such as Google Chrome, Mozilla Firefox, Microsoft Edge, Android Browser and Safari Browser